Evaluating the economics of and business models for metal recycling from waste printed circuit boards in a South African context - Manjengwa, Evelyn Ruvimbo (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.